KONSEP PENDIDIKAN PADA SEKOLAH ALTERNATIF QARYAH THAYYIBAH SALATIGA JAWA TENGAH - Zubaedah Nasucha; Fu’ad Arif Noor (QURROTI, 2020)
This study aims to describe the concept of education in Qaryah Thayyibah Alternative Schools, with the limitations of educational philosophy, educational goals, curriculum, teaching methods, religious education methods, and its graduates. This research was conducted at the Qaryah Thayyibah Alternative School in Salatiga, Central Java. Learning consists of two things, namely a learning society and freedom (free will). The learning societies initiated by Bahruddin, the founder and manager, are understood as people in the community who constantly learn to solve their problems and to improve their quality of life. They study according to their age and occupation level. Old people who are already working to solve problems in their work. Learning citizens have the freedom to determine themselves and choose. All learning citizens, including companions and managers, are free to wish, wish and channel their will and desire.